2017
DOI: 10.4067/s0718-95162017000300013
|View full text |Cite
|
Sign up to set email alerts
|

Diverse salinity responses in Crithmum maritimum tissues at different salinities over time

Abstract: Crithmum maritimum (sea fennel) withstands high salinity, and to better understand how different protective mechanisms against salinity are activated, young seedlings were exposed to increasing concentrations of NaCl (0 to 512 mM) over six weeks. Plant survival and chlorophyll content were reduced at > 85 mM NaCl and growth was affected at ≥ 341 mM NaCl. Relative water content fell and Na + accumulated more in leaves than in roots. Induction of Na + /H + antiporter expression reached a maximum at 427 mM NaCl i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…This fact might explain that the plants did not suffer salt stress or that salinity was not high enough to cause the accumulation of SC. Some studies showed that Crithmum maritimum is able to maintain growth at high salinity levels, even up to 340 mM NaCl [77,78]. However, Ben Hamed et al [79] found that DW biomass of Crithmum begun to reduce even at 50 (4.5 dS m −1 ) mM NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…This fact might explain that the plants did not suffer salt stress or that salinity was not high enough to cause the accumulation of SC. Some studies showed that Crithmum maritimum is able to maintain growth at high salinity levels, even up to 340 mM NaCl [77,78]. However, Ben Hamed et al [79] found that DW biomass of Crithmum begun to reduce even at 50 (4.5 dS m −1 ) mM NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…All experimental procedures were conducted according to the guidelines by the EU Directive 2010/63/EU regarding the protection of animals used for scientific purposes and were applied by FELASA accredited scientists (functions A-D). The two salinities were selected for the following two reasons: (a) 8 ppt is the optimal salinity for rock samphire growth performance [27,28] in hydroponic facilities and (b) 20 ppt is the maximum salinity for the survival and growth for rock samphire.…”
Section: Plants and Fishmentioning
confidence: 99%
“…Rock samphire is a facultative halophyte, meaning that it can grow in a wide range of salinity levels. While it thrives when the irrigation water contains up to 250 mM NaCl, it exhibits reduced growth rates when the salinity exceeds this limit [28]. Nevertheless, rock samphire can survive in seawater [63].…”
Section: Biological Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chlorophyll content reduction is another consequence of salt stress in plants (Taïbi et al, 2016;Hamdani et al, 2017 (Sade et al, 2018). However, it is not possible to conclude whether down-regulation of CV expression is a direct effect of the XGOs.…”
Section: Discussionmentioning
confidence: 99%